Konsep Nation-State dalam Pemikiran Ideologi Politik Melayu Islam pada Abad Ke-19 M (Studi Pemikiran Abdullah bin Abdul Kadir Munsyi (1787-1854) - Andi Chandra Jaya (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2018)
The focus of this study is to answer the subject matter of how the concept of the nation-state according to Abdullah Munsyi in the constellation of Malay Islamic political ideology in the 19th century AD and how is the relevance of the concept of the current Indonesian nation state ? The study used the conscience morale theory of Ernest Renan and the social contract theory initiated by J. J. Roussae. This research is included in the library research category and uses historical approaches and political philosophy. The primary data in this study are Abdullah Musnyi's Hikayat Abdullah book published by Yayasan Karyawan, Kuala Lumpur, Malaysia in 2007 and secondary data, in the form of books, journal articles, papers, and others related to research problems. the findings of the research are: 1). In accordance with the theory of conscience morale Ernest Renan and the social contract theory initiated by J. J. Roussae, Abdullah bin Abdul Kadir Munsyi was the originator of nationalism. Through his most important work, Hikayat Abdullah, he put forward the formulation of Malay identity in the formulation of the nation which was understood as a Malay tribe or race who had the right to be involved in determining the Malay political format not as a community under a political system that was authoritarian. 2). His closeness with the British colonial side, thus forming the liberal thinking he obtained from Raffles and his friends. He not only dismantled the manipulation of royal ideology, but at the same time put forward a new view of the existence of a humanist individual. 3). The understanding of nationality has egalitarian values ​​that are very relevant to the current Indonesian context, especially the values ​​of equality (egalitarianism) in the midst of the emergence of conflicts in various conflicts today. Likewise the concept of nation-state is closely related to nationalism and good governance where good governance is based on the absolute existence of transparency, open participation, and accountability in all state activities at every level of state management, so that a clean government is formed. Keywords: Abdullah Munsyi, Nation-State, and Malay Political ideology